LGBT in the Film “Call Me by Your Name” (2017): Sociological Perspective - Farla Syifa Azzahra; Nugroho, Abdillah (Ethical Lingua: Journal of Language Teaching and Literature, 2024)
This research explores the sociological aspects of the film Call Me by Your Name by investigating indicators of LGBT orientation, factors forming LGBT orientation, and the director's motivation in making the film. This research uses qualitative methods, emphasizing analysis of the film itself as the main source and complementing it with additional sources from existing literature and director interviews. Focusing on the romantic relationship between Elio and Oliver, the researcher revealed that most LGBT indicators in the film are reflected in the behavior and dialogue of the two main characters. Researchers also found that there are internal influences including genetic factors and weak moral and religious values, external influences include the influence of the environment around the main character which is also closely related to same-sex relationships. Director Luca Guadagnino created this film adaptation as an expression of himself inspired by the LGBT-themed novel by André Aciman which aims to present a narrative that encourages growth and change in an individual without being limited by boundaries and differences.